Topologia e Dinâmica de Sistemas Complexos: Transições de Fase e Fenômenos Críticos - Peregrino, Nuno Miguel Melo Crokidakis (2011)
In this thesis we study some complex systems by means of computer simulations and techniques from statistical physics like scaling hypothesis and finite-size scaling analysis. The studied models are diverse and involve classical physical systems (percolation, disordered magnetism) and nonphysical ones (transportation networks, opinion models and epidemic dynamics). Although these models present particular features, all of them undergo phase transitions between distinct states. By means of the above-mentioned techniques we localized the critical points and estimated the characteristic exponents of those models. In addition, the systems were defined on complex and regular topologies. We also discuss some possible extensions of the models studied in this work.